2013
DOI: 10.2478/pjvs-2013-0101
|View full text |Cite
|
Sign up to set email alerts
|

Dietary energy density in the dry period on the metabolic status of lactating cows

Abstract: The aim of the study was to investigate the effect of different energy concentrations in the isonitrogenous diet fed during the dry period on postpartum health, fertility and blood variables. Forty Holstein multiparous cows were dried 56 days before the expected day of calving and assigned to group (M) with moderate energy concentrations of 0.69 UFL/kg DM or to the low-energy group (L) with energy density of 0.61 UFL/kg DM. From the 7d before the expected day of calving until the 21d of lactation, all the cows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
3
1
Order By: Relevance
“…We We found that cows fed high energy diet together with rumen-protected lysine did not differ in pre and postpartum plasma glucose concentrations. In previous study, dry period energy density did not affect glucose concentrations in pre and postpartum cows (Nowak et al, 2013). But our data revealed that interaction between week and energy signi cantly in uenced plasma glucose levels during the transition period.…”
Section: Effect On Plasma Igf-1and Total Bilirubin (Tbil) Concentrationscontrasting
confidence: 72%
“…We We found that cows fed high energy diet together with rumen-protected lysine did not differ in pre and postpartum plasma glucose concentrations. In previous study, dry period energy density did not affect glucose concentrations in pre and postpartum cows (Nowak et al, 2013). But our data revealed that interaction between week and energy signi cantly in uenced plasma glucose levels during the transition period.…”
Section: Effect On Plasma Igf-1and Total Bilirubin (Tbil) Concentrationscontrasting
confidence: 72%
“…However, the cows in the current study were fed the same diet. In general, it might be more difficult to differentiate between the effects of protein or feed restriction in cows since ruminal fermentation occurs in these animals, and data on the influence of nutrient intake during the peripartal period on IGF-I concentrations are conflicting [28,29,23]. Nevertheless, the finding of very low IGF-I mRNA expression but not corresponding low GHR1A mRNA expression has led to the speculation that post-receptor signaling might be negatively regulated in cows with low IGF-I concentrations [12,24].…”
Section: Discussionmentioning
confidence: 99%
“…Few experiments provided details on prepartum diets; hence, the meta-analysis focused on postpartum, early-lactation diets. A further 3 experiments (Colazo et al, 2009;Nowak et al, 2013;Badiei et al, 2014) provided details of precalving diets only and were not included in this analysis. If an experiment reported multiple precalving treatments and a common postcalving diet, the postcalving treatment was used for the multiple groups, but these were included in the analysis as separate treatments.…”
Section: Literature Review and Assessmentmentioning
confidence: 99%